2014
DOI: 10.1111/psyg.12087
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving across the lifespan: comparing caregiver burden, mental health, and quality of life

Abstract: In conclusion, there are important differences between caregiving across the lifespan. Caregiving for children was associated with more depressive symptoms, and caregiving for older adults was associated with higher caregiver burden. Further studies are needed to replicate these findings in other settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 42 publications
0
26
0
2
Order By: Relevance
“…The Zarit Burden Score was used to determine psychosocial stress [5]. The quality of life of relatives and caregivers was assessed using the SF-36 questionnaire [9].…”
Section: Assessment Of Quality Of Life Of Patients and Caregiversmentioning
confidence: 99%
“…The Zarit Burden Score was used to determine psychosocial stress [5]. The quality of life of relatives and caregivers was assessed using the SF-36 questionnaire [9].…”
Section: Assessment Of Quality Of Life Of Patients and Caregiversmentioning
confidence: 99%
“…Literature reviews and meta-analyses confirm the association between greater mental burden and poorer physical and mental well-being: the responsibilities and the stressful experiences related to the caregiving role can cause depression, anxiety, worry and loneliness [17][18][19][20][21][22]. Moreover, family caregivers may also experience a greater mental burden and emotional distress that could impact on fatigue, sleep impairment and unhealthy behaviours [23][24][25][26]. Several studies have demonstrated how caregivers suffer from highly distressing conditions impacting not only on psychological dimensions but also their biological system.…”
Section: Introductionmentioning
confidence: 93%
“…Another institutional and life-course assumption is the view of such unpaid family care as optimal for care receivers and society. Care is institutionalised across the life course, with different expectations, durations and definitions of care at different ages and life stages, and across different cohorts (Pearlin and Aneshensel, 1994; Aneshensel et al, 1995; De Oliveira et al, 2015; Eifert et al, 2016). …”
Section: An Institutional and Life-course Approachmentioning
confidence: 99%
“…He proposes: ‘The basic idea is take the measurement of ecological properties and social processes as seriously as we have always taken individual-level differences’ (Sampson, 2010: 72). There are a few exemplary studies that look at the broader social welfare context (Eichler and Pfau-Effinger, 2009; Jang et al, 2012; Sole-Auro and Crimmins, 2014; Tokunaga et al, 2015) in addition to exemplars viewing care work as a life-course process (Pavalko and Woodbury, 2000; Marks et al, 2008; Barnett, 2015; De Oliveira et al, 2015; Carmichael and Ercolani, 2016; Glauber, forthcoming). However, emphasis on dynamic processes and dynamic institutional contexts could capture what is working and what is not.…”
Section: Implications For Policy-relevant Researchmentioning
confidence: 99%